Sistemas vinculados e o problema da fixação de calibre na ação - Barbosa, Felipe Augusto da Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
The present work deals with gauge symmetries in discrete systems and classical field theories. The text presents the method of counting degrees of freedom in Hamiltonian formalism in order to investigate the problem of gauge fixing at action level, in Lagrangian formalism. The counting of degrees of freedom is done following the Dirac algorithm first exposed in (DIRAC, 1964), and is presented analytically without addressing the phase space of Hamiltonian formalism. The problem of gauge fixing at action level, is developed by following what has been done in (MOTOHASHI; TAKAHASHI, 2016), where a clear criterion for a successful gauge fixing procedure is established. The topics presented are accompanied by examples ilustrating the ideas developed throughout the text

O presente trabalho trata de simetrias de calibre em sistemas discretos e teorias clássicas de campos. O texto apresenta o método de contagem de graus de liberdade no formalismo Hamiltoniano, a fim de investigar o problema de fixação de calibre a nível de ação, no formalismo Lagrangiano. A contagem de graus de liberdade é feita seguindo o algorítimo de Dirac exposto pela primeira vez em (DIRAC, 1964), e é apresentada de forma analítica sem abordar o espaço de fase do formalismo Hamiltoniano. O problema de fixação de calibre a nível de ação é desenvolvido acompanhando o que foi feito em (MOTOHASHI; SUYAMA; TAKAHASHI, 2016), onde um critério claro para um procedimento de fixação de calibre bem sucedido é estabelecido. Os tópicos apresentados são acompanhados de exemplos ilustrando as ideias desenvolvidas ao longo do texto
Bound systems and the problem of caliber clamping in action
Keywords: Gauge theories; Dirac algoritm; Gauge fixing in action; Teorias de Calibre; Algorítimo de Dirac; Fixação de Calibre na Ação; Campos de calibre (Física); Dirac, Equações de; Campos, Teoria de (Física)